Nanomaterials to Enhance Food Quality, Safety, and Health Impact - Lagaron, Jose; Torres-Giner, Sergio; PRIETO, Cristina (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Food quality, safety, and fortification are key aspects to guarantee that foods reach consumers in optimal conditions from the point of view of freshness, microbiology, and health promotion. This book overviews the most recent fundamental and oriented efforts by multidisciplinary researchers and technologists on the application of nanoscience and nanotechnology to generate new added value solutions for the food industry. Nanomaterials to Enhance Food Quality, Safety, and Health Impact provides a valuable guide for both industry and academic researchers interested in the production of healthier, safer, and sustainable food products.